Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1016/j.rmed.2007.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Utility of lung density measurements in the diagnosis of emphysema

Abstract: CT lung density measurements cannot reliably detect the presence of emphysema in an individual. We recommend further investigation into lung density measurements before their widespread use in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 36 publications
7
39
1
Order By: Relevance
“…In cases of discordance, the images were viewed together and a consensus decision reached. Only subjects with definite emphysema were included as having macroscopic disease in subsequent analyses (42).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases of discordance, the images were viewed together and a consensus decision reached. Only subjects with definite emphysema were included as having macroscopic disease in subsequent analyses (42).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, several studies demonstrate that high-resolution CT is more sensitive and specific than commonly used functional tests for the evaluation of initial emphysema in asymptomatic smokers, despite normal or minimal abnormal changes in spirometry, TL CO , or other variables (41,42). In other words, we speculate that it is probable that the definition of COPD according to current guidelines, and hence assignation of our volunteers to one group, could underestimate the presence of early phases or less obstructive phenotypes of the disease.…”
Section: Figurementioning
confidence: 99%
“…CT scanning CT scans of the chest were performed using a single machine (GE Prospeed; GE Yokogawa Medical Systems, Tokyo, Japan), as described previously [25] (see online supplementary material).…”
Section: Feno Measurementsmentioning
confidence: 99%
“…Other studies that classified the COPD phenotype according to HRCT findings found that the cut-off level of the low atten-uation area used to separate non-emphysema from emphysema is quite arbitrary, as it ranges from 0% to 25% (Kasahara et al 2000;Tatsumi et al 2004). Since emphysema can be identified in smokers without airflow limitation on HRCT (Marsh et al 2007), the non-emphysema group in the present study included patients with less than 15% of attenuation area lower than -950 HU at full inspiration. In addition, if a patient showed airflow limitation without evidence of emphysema on HRCT, the patient was categorized into the non-emphysema group, regardless of whether symptoms of chronic bronchitis were present.…”
Section: Discussionmentioning
confidence: 99%